A Comprehensive Revision of Radiation Immunotherapy and the Abscopal Effect in Central Nervous System Metastases: Reassessing the Frontier - Júlia Moscardini-Martelli; Alejandro Rodríguez-Camacho; Jorge Alejandro Torres-Ríos; Juan Marcos Meraz-Soto; José Guillermo Flores-Vázquez; Laura Crystell Hernández-Sánchez; Francisco Javier Lozano-Ruiz; Federico Maldonado-Magos; Dharely Cid-Sánchez; Christian Haydeé Flores-Balcázar; Miguel Ángel Celis-López; Guillermo Axayacatl Gutiérrez-Aceves; et al. (Current Issues in Molecular Biology, 2024)
Seventy years ago, Robin Mole introduced the concept of the abscopal effect to describe a rare phenomenon. This occurs when local radiation triggers an immune-mediated reduction in tumors outside the treated area but within the same organism. Observing this effect has been linked to improved overall and progression-free survival in patients who experience it. While the abscopal effect was once considered rare, it is now being observed more frequently due to the combination of radiation with immunotherapy. As a result, more researchers are exploring this study area, which shows promise for excellent results. This review focuses explicitly on the immunological implications of activating the abscopal effect through ionizing radiation in the central nervous system and explores the potentially involved immunological pathways.